내한 조숙 다수 추파 조사료용 귀리 신품종 풍한 - 한옥규(Ouk Kyu Han); 박형호(Hyong Ho Park); 허화영(Hwa Young Heo); 박태일(Tae Il Park); 서재환(Jae Hwan Seo); 박기훈(Ki Hun Park); 김정곤(Jung Gon Kim); 주정일(Jung Il Ju); 홍윤기(Yu Gi Hong); 정재현(Jae Hyun Jeung); 박남건( Nam Geon Park) (Korean journal of breeding, 2009)
풍한'은 조숙 다수 월동가능 조사료용 귀리 품종을 육성할 목적으로 1999년에 조숙인 '식용귀리'와 대립종인 'PA202-210'을 교배한 F1잡종에 내한성 계통인 'Beltsville 61-150'을 부본으로 인공교배하여 집단 및 계통육종법에 의해 계통을 선발한 후 2004년부터 생산력검정시험 및 지역적응시험을 거쳐 2008년에 육성된 품종으로 주요 특성은 다음과 같다. 1. '풍한'은 잎폭이 중 정도이며, 이삭형은 산수형이고, 종자색은 황백색이다. Punghan' (Avena sativa L.), a winter oat for forage use, was developed by the breeding team at the Department of Rice and Winter Cereal Crop, NICS, RDA in 2008. It was derived from a cross between 'Beltsville 61-150 (IT133501)' and F1 between 'Sikyonggwiri' and 'PA202-210'. A oat cultivar from USA, 'Beltsville 61-150', has a high cold tolerance, while the F1 between 'Sikyonggwiri' and 'PA202-210' has early heading and high yielding with large-size grain. Subsequent enerations followed by the cross were handled in bulk and pedigree selection programs at Suwon and Yeoncheon, respectively. A line, 'SO99013-B-YB-31', was selected for earliness and good agronomic characteristics and designated as a line name of 'Gwiri 60'. The line 'Gwiri 60' was subsequently evaluated for winter hardiness, earliness, and forage yield in five locations, Yesan, Cheongwon, Iksan, Kimjae, and Jeju, from 2006 to 2008 and finally named as 'Punghan'. Over 3 years, the average forage dry matter yield of 'Punghan' harvested at milk-ripe stage was 14.5 ton ha-1, compared with 13.6 ton ha-1 of check cultivar 'Samhan'. 'Punghan' is about 2 days earlier in heading date than check cultivar. 'Punghan' is adapted primarily for winter planting use in the midsouthern regions of Korean peninsula.